2015
DOI: 10.21767/2471-8505.10002
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Student's Experiences in Critical Care Course: A Qualitative Study

Abstract: IntroductionCritical care is the multidisciplinary approach to the management of seriously ill medical, surgical, and obstetric patients [1]. Critical care is an area that presents many learning opportunities for nursing students. However; the need for critical care education at the baccalaureate level is expected to increase [2].Alasad and Ahmad [3] have recommended that students need clinical experiences with critically ill patients. Thus, schools and administrators of the hospitals have an important role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…The importance of mentor-student relationship in enhancing nursing competencies, creating supportive learning environment and increasing students' satisfaction with their clinical placement was reported in previous studies. [1,2,9,11,21] Although clinical placement in the ICU allowed students to participate in patients' caring activities, and helped them to develop their clinical skills, more than half of the students felt that the focus of the practice was on documentation rather than on meeting their learning needs. Moreover, most students viewed focusing on documentation as a hindrance for clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of mentor-student relationship in enhancing nursing competencies, creating supportive learning environment and increasing students' satisfaction with their clinical placement was reported in previous studies. [1,2,9,11,21] Although clinical placement in the ICU allowed students to participate in patients' caring activities, and helped them to develop their clinical skills, more than half of the students felt that the focus of the practice was on documentation rather than on meeting their learning needs. Moreover, most students viewed focusing on documentation as a hindrance for clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…It has been also reported that despite the challenges facing nursing students during critical care placement, students' self-confidence had improved after critical care experience. [9,10] Providing nursing students with quality clinical experience within a supportive clinical learning environment is a major concern for academic institutions. [11] Therefore, understanding nursing students' perception of their critical care experience is important in future planning of successful clinical placement.…”
Section: Introductionmentioning
confidence: 99%
“…Internalization of the powers, roles and responsibilities of nursing by students through receiving a qualified education (2,6,9) is significant for professionalization in nursing (1,6,7) . Clinical training is an essential part of professional nursing education since it ensures the transformation of the knowledge gained through theoretical education into skills, equips students with empathic approach and critical decision-making and effective communication skills, and allows for observing and applying nursing care interventions (3,4,7,(10)(11)(12)(13) .…”
Section: Introductionmentioning
confidence: 99%
“…One of the crucial clinical training settings that help students prepare for the profession is intensive care units (ICU) (2,9,(11)(12)(13)(14) . In these units, students get the opportunity to identify, implement and assess nursing care needs of critical patients, and to observe team collaboration and communication (2,4,(10)(11)(12)(13)(14) . In one of these units, the neurosurgical ICU, students can serve and provide care to neurosurgical patients with different medical monitoring and care needs (3,8) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation